Comparing the efficiency of speech and language therapy and transcranial magnetic stimulation for treating Broca's aphasia - MİDİ, İPEK (My University, 2023)
Objectives: Aphasia is an acquired language-cognitive disorder that highly affects an individual\"s speech, language, and communication skills. Recovery from aphasia requires attentive treatment since it is a long and dynamic process. This study aimed to show interactive benefits of combining classical intervention strategies with new technological approaches and demonstrating their effectiveness. Materials and methods: A total of 40 individuals with Broca\"s aphasia were included in the study. The participants were divided into Application-1 Speech and Language Therapy, Application-2 Transcranial Magnetic Stimulation, Application-3 (consecutive Transcranial Magnetic Stimulation and Speech and Language Therapy), and Application-4 (Control Group) experimental groups, with 10 participants in each group. Results: Analysis indicated that individuals in the group in which Transcranial Magnetic Stimulation and Speech and Language Therapy were applied consecutively had further increases in speech fluency, repetition, and naming scores from pre-test to post-test (p<0.01). Picture naming and quality-of-life communication scores of individuals in the group in which Speech and Language Therapy was performed increased further from pre-test to post-test (p<0.01). Conclusions: The results of the study showed a positive effect on language skills, naming scores, and participation in social life of Turkish-speaking aphasic individuals with the Speech and Language Therapy and Transcranial Magnetic Stimulation methods. The use of Transcranial Magnetic Stimulation alone is insufficient in this context. Although Speech and Language Therapy alone is effective in naming ability, Transcranial Magnetic Stimulation in addition to Speech and Language Therapy significantly increases the gain obtained with therapies.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Kardiyoloji; Nöroloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Cardiovascular; Neurology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; REHABİLİTASYON; KLİNİK NÖROLOJİ; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; REHABILITATION; CLINICAL NEUROLOGY; CARDIAC & CARDIOVASCULAR SYSTEMS; Cerrahi; Rehabilitasyon; Nöroloji (klinik); Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Rehabilitation; Neurology (clinical); Cardiology and Cardiovascular Medicine; Broca's aphasia; Speech and language skills; Speech and language therapy (SLT); Transcranial magnetic stimulation (TMS); Broca’s aphasia; Transcranial magnetic stimulation (TMS); Speech and language therapy (SLT); Speech and language skills